Philippine fiestas [videorecording] - National Commission for Culture and the Arts (Quezon City : Felta.)
A television program featuring fiestas in the Philippines such as the feasts of the Black Nazarene, Ramadan and the different festivals of the Bontoc, Ifugao and the Subanon.
Keywords: Feasts -- Philippines; Festivals -- Philippines